1984
DOI: 10.3102/01623737006002165
|View full text |Cite
|
Sign up to set email alerts
|

Education and Subjective Well-Being: A Meta-Analysis

Robert A Witter,
Morris A Okun,
William A Stock
et al.

Abstract: at is the relation between formal educational attainment and adults' subjective well-being? What factors account for variation in the estimates of this relation? Does education contribute to adult subjective well-being by increasing income or occupational status? To address these questions, we performed a metaanalytic research synthesis. Dependent variables were zero-and first-order correlations between educational attainment and subjective well-being, and independent variables were sample, measure, and study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(92 citation statements)
references
References 16 publications
2
82
0
8
Order By: Relevance
“…A meta-analysis by WITTER et al (1984) found that education is a small but positive contributor to subjective well-being in adults, accounting for 1-3% of the variance. LAYARD (2005) found that education has a small (but significant) direct effect on happiness and that it also affects happiness indirectly by raising personal income.…”
Section: The Role Of Human Capitalmentioning
confidence: 99%
“…A meta-analysis by WITTER et al (1984) found that education is a small but positive contributor to subjective well-being in adults, accounting for 1-3% of the variance. LAYARD (2005) found that education has a small (but significant) direct effect on happiness and that it also affects happiness indirectly by raising personal income.…”
Section: The Role Of Human Capitalmentioning
confidence: 99%
“…In turn, sociological accounts of the life course suggest that institutional opportunities for meaningful activity lag behind the added years that many older persons now experience (Riley, Kahn, & Foner, 1994). Beyond age-related influences on well-being, we also emphasize educational standing, thereby connecting our inquiry to the growing interest in social inequalities-that is, how differential access to resources and opportunities in life influences health and well-being (Adler, McEwen, & Marmot, 1999;Marmot et al, 1997;Witter, Okun, Stock, & Haring, 1984). This multidisciplinary literature increasingly draws on psychological constructs to articulate the mechanisms and processes through which standing in the socioeconomic hierarchy penetrates self-evaluation and life quality (see Ryff & Marshall, 1999).…”
Section: The Contouring Of Well-beingmentioning
confidence: 99%
“…Apart from income, the reported determinants of SWB are culture (see Vitterso, et al, 2005;, age (for example, Blanchflower and Oswald, 2004;Agrawal, et al, 2010), employment status (for example, Clark and Oswald, 1994), social relationships (Diener, et al, 1999;Lucas, et al, 2003;Camfield, et al, 2009), health (for example, Witter, et al, 1984) and education (Agrawal, et al, 2010). For the Indian context, other factors such as caste (see Bosher, et al, 2007) also need to be taken into account.…”
Section: Main Findings Regarding Swbmentioning
confidence: 99%